MINERAL MICROINCLUSIONS IN CUBIC DIAMONDS FROM THE YAKUTIAN DEPOSITS BASED ON ANALYTICAL ELECTRON MICROSCOPY DATA - Titkov S.V.; Gorshkov A.I.; Solodova Yu.P.; Ryabchikov I.D.; Magazina L.O.; Sivtsov A.V.; Gasanov M.D.; Sedova E.A.; Samosorov G.G. (My University, 2006)
In the course of this study, we examined whitish gray crystals from the Yubileinaya kimberlite pipe (samples 1 and 2), gray and greenish yellow crystals from the Aikhal pipe (samples 3 and 4), black crystals from the Udachnaya pipe (sample 5), and orange-brown and brown-gray crystals from the Anabar placer (samples 5 and 6). All crystals were virtually opaque owing to the presence of numerous microinclusions and defects.
Keywords: Yubileinaya kimberlite pipe; Udachnaya pipe